Situation Socio-Demographique, Culturelle Et Comportement Nutritionnel Des Femmes Enceintes En Consultation Prenatale Au Chu De Cocody-Abidjan (Cote d’Ivoire) - Essé Sonia-Estelle; Yeboué Kouamé Hermann; Amoikon Kouakou Ernest (European Scientific Journal, ESJ, 2018)
The objective of this work is to evaluate the socio-demographic and cultural status, and the nutritional behavior of pregnant women received in medical consultation at the Gynecology-Obstetrics Department of the University Hospital Center of Cocody-Abidjan (Côte d'Ivoire). A survey was conducted on a cohort of 504 pregnant women attending antenatal clinics in the period from August 26, 2015 to February 23, 2017. The survey method consisted of collecting information on socio-demographic, cultural and nutritional status, pregnant women, from a survey card. The results showed that these women, whose age varies between 15 and 44 years, are predominantly Ivorian, with 49.23 % of them belonging to the Akan ethnic group. Burkinabe women represent more than half of non-Ivorian women. The Christian women represent 68.25 %, against 29.76 % of Muslim women. Of those surveyed, 82.14 % are single, 82.54 % are literate, compared to 17.86 % married and 17.46 % illiterate. Living conditions have revealed that 3-room apartment buildings are the most inhabited, and many of them enjoy the amenities of a modern home. At the nutritional level, 1.19 % of respondents followed a diet recommended by a doctor and 31.35 % have dietary prohibitions. 0.99 % of this study population regularly consume alcohol. Food groups such as breads, cereals, starchy foods and pulses are the most consumed (68.06 %); meat is more consumed than fish. Fresh fruits and vegetables are less present in the dietary habits of these respondents. From this study, it could be concluded that the respondents have a satisfactory sociodemographic situation. However, civil marriage is not a proof of marital stability. The percentage of divorced could give an indication of this stability, although in Côte d'Ivoire, customary marriage is the most recognized by the community. Finally, in Côte d'Ivoire, eating habits are often known. But it is a good and balanced diet that the population often ignores.